Masa depan civil society di Indonesia: prospek dan tantangan - Halili Halili (Jurnal Civics: Media Kajian Kewarganegaraan, 2006)
This paper aims to discuss on civil society, its prospects and challenges. It is urgent because civil society is a determining factor of lndonesia democratization. Civil society is a society within state which containing social association which has ability to fill public spaces between state and citizen, and interactwith state independt1y, wether indivual or collective. Prospect qf civil societyfarming is determined by establishment ofsome components: 1) existence cf societal autonomy, 2) access ofpublic to state agencies, 3) independent public arena; 4) arena publik yang mandiri, dan keempat arena publik yang terbuka. Prospect of ciuil society deuelopmentis influenced by optimalization ofsome factors: 1) establishment of, democratic families, 2) growth of roles of non government organization toward both state and citizen, 3) increase of intellectual middle class, especially students, and 4) implementation of political education formally (e.g. civic or citizenship education) and informally. The challenges of future of civil society are: 1) high of social fragmentation among people, 2) limited distribution of development results infold ofeconomy, social, and education, and also 4) paternalistic culture which is stiO strong among society.